Construction of P1-Derived Artificial Chromosome and Yeast Artificial Chromosome Contigs Encompassing the DFNB7 andDFNB11 Region of Chromosome 9q13–21 - Greinwald, John H.; Scott, Daryl A.; Marietta, Jacquie R.; Carmi, Rivka; Manaligod, Jose; Ramesh, Arabandi; Zbar, Ross I.S.; Kraft, Michelle L.; Elbedour, Khalil; Yairi, Yael; Musy, Maurice; Skvorak, Anne B.; et al.

(untitled) (Genome Research, 1997)
DFNB7 and DFNB11, two loci for autosomal recessive nonsyndromic hearing loss (ARNSHL), have been mapped to chromosome 9q13–21 in separate consanguineous families. Using a radiation hybrid map, we have determined the correct marker order in the DFNB7/11 region and have demonstrated that theDFNB11 locus resides within a redefined DFNB7interval. The gene(s) responsible for ARNSHL at these loci resides within an ∼1 cM interval bounded by markers D9S1806(centromeric) and D9S769 (telomeric). A recently discovered Indian family confirms the new telomeric boundary. To assist in the identification and cloning of candidate genes, YAC and PAC contigs were constructed. A total of 19 YAC and 23 PAC clones were utilized to span the affected region and ensure double coverage throughout. Twenty-two previously published STSs and 21 new STSs were used to determine marker order and confirm the integrity of the contig. Using a positional cloning strategy we have identified three cochlear expressed genes that map to the DFNB7/11 interval.